STROKE ISKEMIK DENGAN MANIFESTASI DIZZINESS/VERTIGO TERISOLASI - Diyan Anita Sari; Sri Sutarni; Ismail Setyopranoto (PERDOSNI, 2020)
ISCHEMIC STROKE PRESENTS WITH ISOLATED DIZZINESS/VERTIGOABSTRACTDizziness/vertigo, unstable walking or loss of balance are symptoms in about 50% of stroke cases. However, only about 20% are accompanied by focal neurological signs. In the last decade, there is increasing evidence that vertigo can be the only ischemic symptom of posterior circulation stroke without a focal sign. The purpose of this systematic review is to examine the literature on ischemic stroke with the manifestation of isolated dizziness/vertigo. The literature search is done through several electronic database (Pubmed, Ebscohost, and Proquest) from 2000 to 2017 using keywords; isolated vertigo, isolated dizziness, ischemic stroke, vertebrobasilar, posterior stroke, magnetic resonance imaging (MRI). Six articles were obtained that meet the criteria. Approximately 9-10% of patients with isolated dizziness/vertigo who had a history of vascular risk factors, found to have infarct lesions from MRI diffusion weighted imaging (DWI) examination. In this case, the territory of posterior inferior cerebellar artery (PICA) is most often involved. Acute ischemic stroke can not be excluded only on the basis of negative DWI examination results. Head impulse, nystagmus, and test of skew (HINTS) plus examination may identify acute vestibular syndrome with a central cause with better accuracy than MRI DWI at the onset of symptom.Keywords: Acute vestibular syndrome, ischemic stroke, isolated dizziness, isolated vertigo, posterior circulation strokeABSTRAKDizziness/vertigo, berjalan tidak stabil atau kehilangan keseimbangan merupakan gejala pada sekitar 50% kasus stroke. Namun, hanya sekitar 20% disertai tanda neurologis fokal. Pada dekade terakhir, semakin banyak bukti bahwa vertigo dapat sebagai satu-satunya gejala iskemik sirkulasi posterior tanpa tanda fokal. Tujuan penulisan tinjauan sistematik ini adalah untuk mengkaji literatur tentang stroke iskemik dengan manifestasi hanya dizziness/vertigo terisolasi. Pencarian literatur dilakukan melalui database elektronik (Pubmed, Ebscohost, dan Proquest) dari tahun 2000 hingga 2017 dengan kata kunci; isolated vertigo, isolated dizziness, ischemic stroke, vertebrobasilar, posterior stroke, magnetic resonance imaging (MRI). Didapatkan 6 artikel yang memenuhi kriteria. Sebanyak 9-10% dari pasien dengan dizziness/vertigo terisolasi yang memiliki riwayat faktor risiko vaskular, ditemukan lesi infark dari pemeriksaan MRI diffusion weighted imaging (DWI). Dalam hal ini, teritori posterior inferior cerebellar artery (PICA) yang paling sering terlibat. Stroke iskemik akut tidak dapat disingkirkan hanya berdasar hasil pemeriksaan DWI negatif. Pemeriksaan head impulse, nystagmus, and test of skew (HINTS) plus dapat mengidentifikasi sindrom vestibular akut dengan penyebab sentral dengan akurasi yang lebih baik dibanding MRI DWI di awal onset gejala.Kata kunci: Dizziness terisolasi, sindrom vestibular akut, stroke iskemik, stroke sirkulasi posterior, vertigo terisolasi